The Oxford Handbook of Positive Psychology 2009
DOI: 10.1093/oxfordhb/9780195187243.013.0041
|View full text |Cite
|
Sign up to set email alerts
|

Furthering the Science of Gratitude

Abstract: In this chapter, we sought to strengthen the science of gratitude. We suggest effective approaches for studying gratitude, present a theoretical framework for researching gratitude, review recent gratitude research, and suggest directions and questions for future research, all in an attempt to encourage research on this important virtue. After presenting a brief historical background of gratitude, we define state and trait gratitude and describe several useful measurement tools. We review research that has exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 0 publications
2
47
0
2
Order By: Relevance
“…First, death reflection may be a good exercise for enhancing state gratitude. Although experimental studies have shown that enhancing gratitude results in increased subjective well-being (e.g., Emmons & McCullough, 2003; for a review, see Watkins et al, 2009), more research needs to investigate exercises that might enhance gratitude. Death reflection appears to be one way that individuals can The Journal of Positive Psychology 159 enhance their appreciation and gratitude for life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, death reflection may be a good exercise for enhancing state gratitude. Although experimental studies have shown that enhancing gratitude results in increased subjective well-being (e.g., Emmons & McCullough, 2003; for a review, see Watkins et al, 2009), more research needs to investigate exercises that might enhance gratitude. Death reflection appears to be one way that individuals can The Journal of Positive Psychology 159 enhance their appreciation and gratitude for life.…”
Section: Discussionmentioning
confidence: 99%
“…Trait gratitude measures are strongly correlated with various measures of subjective well-being (e.g., McCullough, Emmons, & Tsang, 2002;Watkins, Woodward, Stone, & Kolts, 2003b;Wood, Joseph, & Maltby, 2008), longitudinal studies have found that gratitude predicts increased well-being over time, and gratitude is one of the strongest predictors of happiness amongst the strengths identified by the Values In Action project (Park, Peterson, & Seligman, 2004;. Furthermore, experimental studies have provided promising evidence that gratitude exercises may actually enhance immediate mood state (Watkins et al, 2003b), and long-term subjective well-being (Emmons & McCullough, 2003;Froh, Sefick, & Emmons, 2008;Lyubomirsky, Sheldon, & Schkade, 2005;Seligman, Steen, Park, & Peterson, 2005, for a review, see Watkins, Van Gelder, & Frias, 2009). Thus, not only is there a strong tendency for grateful individuals to be happy, but now there also appears to be some evidence that gratitude causes enhanced subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Gratitude is conceptualized both state and trait in the literature (Watkins et al, 2009). State gratitude is related to recognition of the benefit.…”
Section: Gratitude: An Overviewmentioning
confidence: 99%
“…State gratitude is related to recognition of the benefit. Emmons (2003) and McCulluogh et al (2001) suggested and empirically showed that individuals feel positive emotional reaction when they gain a benefit from benefactor or appreciation of good things enhances state gratitude (Watkins et al, 2009). While state gratitude captures the gratitude that may change based on contextual factors, trait gratitude symbolize generally experienced gratitude.…”
Section: Gratitude: An Overviewmentioning
confidence: 99%
“…Interventions such as Three Good Things prompt positive reminiscence by asking participants to list good things that happened during their day, and they have been shown to increase positive emotions. These memory processes are thought to be important in appreciative functioning (Watkins et al 2009). Using a cross-sectional design with 122 participants, Watkins et al (2004) found that appreciative functioning is associated with a tendency to recall positive, rather than negative, events.…”
Section: The Attention and Awareness Domainmentioning
confidence: 99%